Juger de l'efficacité des financements en fonction de leurs finalités: Quatre arbitrages de la coopération internationale pour le développement - Sylviane Guillaumont Jeanneney (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– The objectives of international development cooperation have undergone profound changes in recent decades. To the traditional goals constituted by the fight against poverty and the development of less developed countries the promotion of global public goods has been added. It is in terms of all of these purposes that this article attempts to assess the effectiveness of this cooperation, subject to four trade-offs: between the development or convergence of economies and the immediate well-being of the poorest; between this development and the preservation of global public goods; between preventive actions and curative actions; between the interests of the countries receiving aid and those of the international community.
Keywords: 330